ADMINISTRATIVE COMPUTERIZED FITNESS CENTER PT. BINA WANA SARANA JAKARTA - John Henry Ray; Hariyanto Hariyanto, S.Kom.,MMSI. (Jurnal Sistem Informasi, 2002)
Advances in computer technology is felt very fast, but the application of computers ineveryday life, especially in the job has not run as expected for most Indonesianpeople, the computer is still the foreign goods and expensive, therefore we needpromoted, the use of computers in all fields of work. Computers helpful tasks we do,especially tasks requiring high precision and accuracy and the speed at which reliable.The title of this research writing "Computerized Fitness Center on PT. Bina SaranaWana. " The author tries to apply the use of computers in the existing system ofmanual administration.